2019
DOI: 10.1016/j.actbio.2019.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Robust antigen-specific tuning of the nanoscale barrier properties of biogels using matrix-associating IgG and IgM antibodies

Abstract: Biological hydrogels (biogels) are selective barriers that restrict passage of harmful substances yet allow the rapid movement of nutrients and select cells. Current methods to modulate the barrier properties of biogels typically involve bulk changes in order to restrict diffusion by either steric hindrance or direct high-affinity interactions with microstructural constituents. Here, we introduce a third mechanism, based on antibody-based third party anchors that bind specific foreign species but form only wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…They can also retard the migration of bacteria across the gel. 38 Similar IgG-and IgM-mediated immobilization of nanoparticles has been found in alginate. 47 4.1.1.…”
Section: Third-party Modulatorsmentioning
confidence: 60%
See 1 more Smart Citation
“…They can also retard the migration of bacteria across the gel. 38 Similar IgG-and IgM-mediated immobilization of nanoparticles has been found in alginate. 47 4.1.1.…”
Section: Third-party Modulatorsmentioning
confidence: 60%
“…Motivated by studies with various mucus secretions, we explored whether IgG and IgM could also facilitate trapping in other biogels and discovered that both mediated effective trapping of virus-sized nanoparticles in Matrigel as well as matrix composed of laminin/entactin. 38 Notably, IgM antibodies have 51 potential glycosylation sites. Of these, 31 are glycosylated with complex glycans terminated in galactose or sialic acid and are 80% occupied.…”
Section: Third-party Modulatorsmentioning
confidence: 99%
“… 18 , 42 This theoretical prediction was confirmed by experiments using mouse mucus and other biogels that showed IgM exhibited considerably greater muco-trapping potencies than IgG. 52 , 57 , 58 …”
Section: Modest Ab-mucin Affinity Key To Maximal Muco-trapping Potencymentioning
confidence: 71%
“…Muco-trapping may be part of a greater matrix-trapping functions of Ab, as evident by our work investigating IgG- and IgM- mediated trapping in Matrigel®, laminin, collagen, alginate and agarose. 44 , 52 , 58 Continued advances in the chemistries involved with Fc-mucin interactions will likely lead to improved next generation Ab that can enable much more potent trapping in mucus, similar to efforts over the past two decades that have led to IgG-Fcs enabling prolonged circulation and tuning specific Fc effector functions.…”
Section: Discussionmentioning
confidence: 99%
“… 131 In addition, microrheology was used to develop IgG-loaded biological gels composed of matrigel, laminin, and entactin as barriers to virus-like nanoparticles and bacteria. 132 It was demonstrated that these barrier hydrogels reinforced with IgG specific to Salmonella reduced bacterial penetration to the underlying tissue and significantly reduced infectivity.…”
Section: Novel Biomaterials Designed Through Microrheologymentioning
confidence: 99%